2011
DOI: 10.1302/0301-620x.93b9.26598
|View full text |Cite
|
Sign up to set email alerts
|

Revision total hip arthroplasty using a Kerboull-type acetabular reinforcement device with bone allograft

Abstract: We retrospectively reviewed 40 hips in 36 patients who had undergone acetabular reconstruction using a titanium Kerboull-type acetabular reinforcement device with bone allografts between May 2001 and April 2006. Impacted bone allografts were used for the management of American Academy of Orthopaedic Surgeons Type II defects in 17 hips, and bulk bone allografts together with impacted allografts were used for the management of Type III defects in 23 hips. A total of five hips showed radiological failure at a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 20 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…There are two main concepts in acetabular reconstruction: one is to achieve rigid containment and recover bone stock using metal mesh or reinforcement devices with bone grafting to stabilize the cemented cup and the other is to achieve bone ingrowth using a cementless cup with or without bone grafting or augmentation devices. Surgical techniques representative of the former concept include a cemented cup with a reinforcement plate [ 5 , 6 ], a cage [ 7 ], or impaction bone grafting [ 8 , 9 ]. The success of these techniques depends on achieving adequate initial stability followed by a biological response of graft incorporation and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main concepts in acetabular reconstruction: one is to achieve rigid containment and recover bone stock using metal mesh or reinforcement devices with bone grafting to stabilize the cemented cup and the other is to achieve bone ingrowth using a cementless cup with or without bone grafting or augmentation devices. Surgical techniques representative of the former concept include a cemented cup with a reinforcement plate [ 5 , 6 ], a cage [ 7 ], or impaction bone grafting [ 8 , 9 ]. The success of these techniques depends on achieving adequate initial stability followed by a biological response of graft incorporation and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Kawanabe et al reported that the 10-year survival rates using the Kerboull plate in morselized and bulk graft group were 53% and 82%, respectively [16]. Akiyama et al reported that the survival rate using the KT plate with bulk and morselized allografts at 10 years was 87% [14]. Hori et al reported a survival rate of 92.3% for the KT plate with bulk and morselized allografts at 10 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…because the KT plate is more elastic than Kerboull plate, the yield points of the inferior hook and of the pallet of the KT plate were reached at displacements of approximately 1 mm and 4 mm, respectively [14]. The Kerboull plate was used in 9 hips and the KT plate was used in 31 hips.…”
mentioning
confidence: 99%
“…Slightly better results were published by Akiyama et al, with the same type of reinforcement ring and bone grafts. Survival rate, calculated using radiological failure or revision, was 87 % at ten years [15], but their patients had less severe acetabular bone defects than patients of Hori et al [14]. Bohm and Banzhaf reported a rate of 89 % with three reconstruction alternatives in 103 cases that were followed up for 0.3–13 years [16].…”
Section: Discussionmentioning
confidence: 99%